Machine Maintenance Design using Markov Chain Method to Reduce Maintenance Costs - Syakhroni, Akhmad; Adi Darmawan, Rizka Fajar; Marlyana, Novi (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2021)
PT. XYZ is a company that focuses on construction with ready mix concrete product (cast). The problem faced by the company is that the schedule is not suitable for machine maintenance activities so that it still results in high maintenance costs incurred by the company. By using the markov chain method can plan maintenance time in order to reduce downtime so as to minimize maintenance costs. The results obtained by the proposal for the company are for proposal I it takes 49.78 hours = 50 hours at a cost of Rp. 16,984,605, the cost savings of Rp. 73,545,395 (81.24%). Schedule for each machine such as wheel loaders every 14,009 hours, batching plant machines every 16,604 hours, truck mixer machines every 19,168 hours. Scheduling the second proposal will take 26.62 hours = 27 hours at a cost of Rp. 9,080,664, the cost savings of Rp. 81,449,336 (89.97%). Schedule for every machine such as wheel loaders every 7,490 hours, batching plant machines every 8,877 hours, mixer truck machines every 10,248 hours. Judging from the results obtained, the recommendation given is